Reduced floral diversity and predominance of exotic species in the urban trees of the Esmeraldas canton, Ecuador - Cali Ligua, Valeria Lissette (2025)
The urban trees of the Esmeraldas canton in Ecuador fulfills essential ecological and social functions, buttheir current state is poorly understood. This study aimed to characterize the diversity, composition, and coverage of urban public green spaces. A forest inventory was conducted in 50 representative areas, recordinga total of 1,450 trees belonging to 20 tree species, distributed among 13 families. The results show a markedpredominance of introduced species (90%) compared to only 10% native species, with Adonidia merrillii being the most abundant, having an ecological importance value index of 38.34%. The Fabaceae family wasthe most represented. Urban vegetation coverage was 78,276 m² over a total surface area of green spacesof 352,421 m², with an urban green index of 2.06 m²/hab, a value well below the minimum of 9 m²/hab-1 recommended by the World Health Organization. Biodiversity indices reflected low to medium levels: Margalef(2.61), Simpson (0.63), and Shannon-Wiener (1.56). Taken together, these results indicate an unbalancedtree population, dominated by exotic species and with low diversity, which poses ecological and functionalrisks for the future. It is concluded that it is necessary to implement urban planning policies focused on diversifying tree populations, incorporating native species, and increasing vegetation cover as priority measuresto improve the sustainability, resilience, and environmental quality of the urban environment in the Esmeraldas canton.